"Are these adult doctors gonna know me?" Experiences of transition for young people with a liver transplant. (25th August 2016) - Wright, J.; Elwell, L.; McDonagh, J. E.; Kelly, D. A.; Wray, J.
Abstract: Excellent survival rates in paediatric LTx have resulted in increasing numbers of young people transferring from paediatric to adult care. Understanding the mechanisms of successful transition is imperative for ensuring good long‐term outcomes and developing services for young people. Semi‐structured interviews were conducted with 17 young people (10 females; age range: 15.2–25.1 years). Eight were within 1 year of transferring to adult services; nine had transferred. Interviews were analysed using IPA. Analysis revealed two major themes in both pre‐ and post‐transfer groups: "relationships with healthcare professionals" and "continuity of care." Young people experienced difficulty ending relationships with paediatric clinicians and forming new relationships with adult clinicians. They expressed frustrations over a perceived lack of continuity of care after transfer and a fear of the unknown nature of adult services. The importance of a holistic approach to care was emphasized. Interventions are needed to support young people in transition, particularly in ending relationships in paediatric care and forming new relationships in adult care. Young people need help to develop strategies to cope with the different approaches in adult services. Interventions to provide clinicians with skills to communicate and engage with young people are imperative.